Effects of Antimicrobial Peptide Microcin C7 on Growth Performance, Immune and Intestinal Barrier Functions, and Cecal Microbiota of Broilers - Dai, Ziqi; Shang, Lijun; Wang, Fengming; Zeng, Xiangfang; Yu, Haitao; Liu, Lu; Zhou, Jianchuan; Qiao, Shiyan (Frontiers in Veterinary Science, 2022)
Microcin C7 is an antimicrobial peptide produced by Escherichia coli cells, composed of a heptapeptide with a modified adenosine monophosphate. This study was performed to evaluate the effects of Microcin C7 as a potential substrate to traditional antibiotics on growth performance, immune functions, intestinal barrier and cecal microbiota of broilers. In the current study, 300 healthy Arbor Acres broiler chicks were randomly assigned to 1 of 5 treatments including a corn-soybean basal diet and basal diet supplemented with antibiotic or 2, 4 and 6ppm Microcin C7. Results showed that Microcin C7 significantly decreased F/G ratio of broilers, significantly increased the levels of serum cytokine IL-10, immunoglobulin IgG and IgM, ileal sIgA secretion, significantly decreased the level of serum cytokine TNF-α. Microcin C7 significantly increased villus height and V/C ratio, significantly decreased crypt depth in small intestine of broilers. Microcin C7 significantly increased gene expression of tight junction protein Occludin and ZO-1, significantly decreased gene expression of pro-inflammatory and chemokine TNF-α, IL-8, IFN-γ, Toll-like receptor TLR2, TLR4 and downstream molecular MyD88 in jejunum of broilers. Microcin C7 significantly increased the number of Lactobacillus, decreased the number of total bacteria and E.coli in the cecum of broilers. Microcin C7 also significantly increased SCFA and lactic acid levels in ileum and cecum of broilers. In conclusion, diet supplemented with Microcin C7 significantly improve growth performance, strengthen immune functions, enhance intestinal barrier, and regulate cecal microbiota of broilers. Therefore, antimicrobial peptide Microcin C7 has the potential to be an ideal candidate to antibiotic.